Fueling soccer players: A scoping review and audit of literature related to soccer-specific guidelines for carbohydrate intake - Foo, W. L.; Tester, E.; Close, G. L.; Areta, J. L.; Morton, J. P. (Sports Medicine, 2025)
Background: Professional soccer players are advised to consume 3-8 g kg-1 body mass day-1 of carbohydrate (CHO) on the basis of training demands, fixture schedule and personal objectives. However, owing to the lack of randomized controlled trials on elite players, these guidelines largely rely on data interpretation and practitioner experience.